The Effect of Good Corporate Governance and Information Technology Implementation on Operational Cost Efficiency, With Firm Size as a Moderator - I Gusti Ayu Agung Nararatna Mirah Nandini; Naniek Noviari (International Journal Of Economics Social And Technology, 2026)
Operational cost efficiency is essential for improving profitability and sustaining competitiveness, particularly in the food and beverage manufacturing industry, which is characterized by complex production processes and high operating costs. This study examines the effects of Good Corporate Governance (GCG) and Information Technology (IT) implementation on operational cost efficiency, with firm size as a moderating variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2020–2025. The study employs a quantitative approach using purposive sampling, resulting in 34 companies and 204 panel observations. GCG was measured using a four-component governance index, IT implementation through content analysis, and operational cost efficiency using the Operating Cost Efficiency Ratio. Data were analyzed using Moderated Regression Analysis (MRA) with panel data regression in EViews. The results show that GCG and IT implementation positively and significantly improve operational cost efficiency. Firm size does not moderate the relationship between GCG and operational cost efficiency but strengthens the positive effect of IT implementation. The novelty of this study lies in examining the joint role of GCG, IT implementation, and firm size in explaining operational cost efficiency in the Indonesian food and beverage manufacturing sector. The findings contribute to the literature on governance and digital transformation while providing practical insights for managers to enhance operational efficiency through stronger governance and effective IT adoption.